Optimizing second-line endocrine-based treatment in HR positive HER2 negative metastatic breast cancer: a comprehensive expert statement from the Gulf Cooperation Council Region - Alshehri, Ahmed; Altwairgi, Abdullah Khalaf; AlTourah, Abdulwahab; Alwbari, Ahmed; Chehal, Aref; Calaud, Francois; Al-Hashem, Hashem; Marashi, Husam; Elsamany, Sherif; Tirmazy, Syed Hammad (Frontiers in Oncology, 2026)
Optimizing second-line therapy for hormone receptor-positive (HR+) and human epidermal growth factor receptor 2–negative (HER2-negative) metastatic breast cancer (mBC) in the Gulf Cooperation Council (GCC) is challenged by variations in diagnostic capacity, drug accessibility, comorbidities, and treatment pathways compared with other regions. While international guidelines provide an overarching evidence framework for breast cancer management, their practical application at the regional level often requires adaptation to local healthcare resources. There is an unmet need to optimize the treatment sequencing strategies for patients with HR+/HER2-negative mBC in the GCC region through expert guidance. Given this context, a virtual advisory board involving 10 oncologists from the GCC region was convened in November 2024. The panel aimed to review current evidence and develop pragmatic, implementable recommendations for second-line management. This consensus uniquely contextualizes global evidence for GCC-specific healthcare constraints, addressing gaps in diagnostic access, affordability, and real-world feasibility, while providing treatment recommendations that help clinicians refine therapeutic strategies and incorporate patient preferences for improved outcomes. The panel recommends early genomic testing (PIK3CA, AKT, BRCA, ESR1) to guide therapy, prioritizing targeted agents such as oral SERDs and PI3K/AKT inhibitors in second-line sequencing, cautious use of alpelisib in diabetic patients, and incorporating patient preferences through shared decision-making and multidisciplinary care.